Inhabiting the Multiple Places, Spaces, and Time for Learning - Maggie Hartnett; Lucila Carvalho; Heather Lamond; Fiona Murray; Duncan O'Hara; Alison Fields (Flexible Learning Association of New Zealand, 2018)
This editorial of the Journal of Open, Flexible and Distance Learning (JOFDL) provides an overview of the FLANZ2018 biennial conference held at Massey University, Palmerston North, New Zealand, 9-11 April, 2018. The conference theme, From Inception to Infinity: Inhabiting the Multiple Places, Spaces and Time for Learning provided the context for the five keynote speakers to explore the opportunities for learning that are emerging from the rapidly changing world of digital technologies. An overview of their presentations is discussed below. These, in addition to the two extended conference papers in the issue, offer insights into emerging learning opportunities. The other contributions in this issue extend our understanding of how digital technologies are influencing learning and teaching in different contexts.